2015
DOI: 10.1109/jbhi.2015.2417754
|View full text |Cite
|
Sign up to set email alerts
|

A Passive Biodegradable Implant for Subcutaneous Soft Tissue Trauma Monitoring

Abstract: In-body medical devices can play an important role in clinical monitoring and diagnosis of diseases. Wireless devices implanted within a patient have to be physically small, and must overcome the challenges of having a little or no onboard electrical power and the highly attenuating electromagnetic propagation environment which is the human body. In this paper, we investigate the use of biodegradable implant to monitor the healing of soft-tissue trauma and to allow early stage diagnosis of infection. The impla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 29 publications
(30 reference statements)
0
13
0
Order By: Relevance
“…A biodegradable and implantable RF identification tag has been created as another wireless operation mode. [89] The device can be implanted to observe tissue healing and to permit early i) The layers of resistive sensors. ii) Image of the sensing element with serpentine traces.…”
Section: Design and Development Of Implantable Biodegradable Biosensorsmentioning
confidence: 99%
“…A biodegradable and implantable RF identification tag has been created as another wireless operation mode. [89] The device can be implanted to observe tissue healing and to permit early i) The layers of resistive sensors. ii) Image of the sensing element with serpentine traces.…”
Section: Design and Development Of Implantable Biodegradable Biosensorsmentioning
confidence: 99%
“…Information is, therefore, stored in their forward and reflected frequency response and communication between the tag and the interrogator takes place using the backscattering mechanism [5,15]. A single uniform cross-shaped resonator similar to the one presented in [8] and used in the literature for FSS applications [16] has been designed. Fig.…”
Section: Theory and Designmentioning
confidence: 99%
“…Despite the growing interests in RFID technology in various sectors of industry, few attempts have been made to use selfresonant tags as an implantable device. It has been suggested in [8,9] that backscattering tags could be employed as a biodegradable subcutaneous implant for early-stage diagnoses of post-surgical infection. Nevertheless, it has been shown that the backscattered signal was highly attenuated by the biological medium and some signal detectability issues have been encountered.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations